Cloud seeding over Tasmania : a long-term evaluation and modelling plausibility study - Morrison, Anthony Edward (Monash University. Faculty of Science. School of Mathematical Sciences, 2010)
Initially, an analysis of cloud seeding activity for the period 1960-2005 over a hydro-electric catchment (target) area located in central Tasmania is presented. The analysis is performed using a double ratio on monthly area averaged rainfall for the months May-October. Results indicate that increases in monthly precipitation are observed within the target area relative to nearby controls during periods of cloud seeding activity. Ten independent tests were performed and all double ratios found are above unity with values that range from 5-14%. Nine out of ten confidence intervals are entirely above unity and overlap in the range of 6-11%. Nine tests obtain levels of significance greater than the 0.05 level. If the Bonferroni adjustment is made to account for multiple comparisons, six tests are found to be significant at the adjusted alpha level. Secondly, the cloud structure associated with two frontal passages/cloud seeding events over the Southern Ocean and Tasmania is investigated. The Weather Research and Forecasting (WRFV2.2.1) model is evaluated using remote sensed and in-situ observations within the post frontal airmass. The evaluated cases are then used to investigate numerically the prevalence of supercooled and mixed phase clouds over Tasmania and the ocean to the west. The simulations produce marine stratocumulus like clouds with maximum heights of between 3 and 5km. These are capped by weak temperature and strong moisture inversions. When the inversion is at temperatures warmer than -10 C, WRF produces wide spread supercooled cloud fields with little glaciation. This is consistent with the limited in-situ observations. When the inversion is at higher altitudes, allowing cooler cloud tops, glaciated (and to a lesser extent mixed phase) clouds are more common. The sensitivity of the simulations to certain bulk microphysical assumptions is explored, the findings indicate the results are relatively insensitive to the parameters investigated. Finally, a MODIS based climatology of Southern Ocean clouds south of mainland Australia is presented, for the region 30-60S and 100-160E. Particular emphasis is placed on observations of supercooled clouds. Results are compared with those from the North Pacific region (30-60N, 160-220E) as a point of comparison. The findings presented are consistent with an earlier study by cite{Mace_cloudsat}, between 40-60% of clouds that exist over the Southern Ocean west of Tasmania are low with tops <3km and cloud top temperatures ~0 C. Supercooled clouds are more common at the high latitudes, the island of Tasmania (situated in the lower latitude bands) modifies clouds sufficiently so that these resemble more closely those within the higher latitude bands. Little annual variability is observed. The North Pacific region resembles the Southern Ocean, however a greater seasonal variability is observed. In general, a supercooled cloud top is observed ~20% of the total time over the Southern Ocean and North Pacific. Mixed phase clouds are more rare, occurring <10% of the total time. Over western Tasmania, supercooled clouds exist ~25% of the time during winter months.